Diseño de un plan de mantenimiento para máquina compactadora de material reciclable en la empresa recuperadora la mejor JB S.A.S. - Riasco Severiche, Leonelis Francisca (Universidad Antonio Nariño, 2023)
In the municipality of Maicao, department of La Guajira, there is a company in charge of the recycling process, called Recoveradora la Mejor JB S.A.S. Thanks to the compaction machines that this company has, this activity is carried out in a more simplified way and with greater precision, the Machines play an important role in the development of any company, in order to produce high-quality and competitive products in the market, they depend on the operation of the machines and the personnel who work there. These equipment that carry out the recycling process do not have adequate maintenance or monitoring of the operation of the equipment, therefore, it is proposed to carry out and structure a preventive maintenance plan to guarantee the operation of the machines within the necessary capacity. This maintenance aims to reduce downtime and excessive depreciation of a company's properties as much as possible, by keeping equipment and facilities in optimal operating conditions. The application of this type of maintenance is planned, prepared and programmed, so its implementation makes it possible to discover and correct possible failures and their origin, instead of repairing them when they have already occurred.